Effects of ecological restoration on soil biogenic elements and their ecological stoichiometry in the Yellow River Delta, China - Li, Dongxue; Li, Yi’na; Xie, Yiliang; Cui, Baoshan; Ning, Zhonghua; Zhang, Shuyan; Bi, Zhenggang; Fu, Shouqiang; Che, Chunguang (Frontiers in Marine Science, 2022)
Coastal wetlands serve as sources and sinks of carbon, nitrogen, phosphorus, and sulfur, and their ecological stoichiometry intuitively indicates the biogeochemical cycle process of the region. This study investigated the changing trend of the contents of soil organic carbon (i.e., SOC), total nitrogen (i.e., TN), total phosphorus (i.e., TP), and total sulfur (i.e., TS) and their ecological stoichiometric ratios in 2019-2021 in the Yellow River Delta (including north and south banks) under the Internationally Important Wetland Biodiversity Conservation Project by conducting field surveys and experiments. The results showed that SOC, TN, and TP showed the highest content in the North Unrestoration, while the TS content appeared highest in the North Restoration. In addition, ecological restoration improved the biogenic element stability in both banks and improved the stability of ecological stoichiometry on the north bank while decreasing the ecological stoichiometry stability on the south bank. Notably, the changing trend of soil C/S in the North Unrestoration exhibited a considerably different profile similarity from the North Restoration, which indicates that the ecological restoration changed the wetland ecosystem from the perspective of soil C/S. Furthermore, the high content of soil biogenic elements SOC and high ratio of soil ecological stoichiometry C/N and C/S in the Yellow River Delta induce that they are more sensitive to environmental change. Over the three years, the contributions of soil moisture content, soil salinity, and pH to soil biogenic element contents and their stoichiometric ratios were 32.20%, 49.30%, and 18.50% on the north bank, respectively, and 85.70%, 8.50%, and 5.80% on the south bank, respectively. This study implies that ecological restoration generally has a positive effect on the soil biogenic element contents and their ecological stoichiometry in the Yellow River Delta and provides a reference for delta restoration.